Biochemical Constituents of Phaleria macrocarpa (Leaf) Methanolic Extract Inhibit ROS Production in SH-SY5Y Cells Model - Ibrahim Maina Hassan; Wan Norhamidah Wan Ibrahim; Ferdaus Binti Mohamat Yusuf; Siti Aqlima Ahmad; Syahida Ahmad (Biochemistry Research International)
Background. Reactive oxygen species generation in mammalian cells profoundly affects several critical cellular functions, and the lack of efficient cellular detoxification mechanisms which remove these radicals may lead to several human diseases. Several studies show that ROS is incriminated as destructive agents in the context of the nervous system especially with advance in age leading to neurodegeneration. Current treatments of this disease are not effective and result in several side effects. Thus, the search for alternative medicines is in high demand. Therefore, the aim of this study is to evaluate the reactive oxygen inhibitory effect of Phaleria macrocarpa 80% (leaf) extract. Methods. The leaf was extracted with 80% methanol. Cytotoxicity studies were carried out using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), and ROS inhibitory activities were evaluated using dichlorofluorescein diacetate (DCF-DA) assay in the SH-SY5Y cells model. Results. The result revealed ROS inhibitory activities of the crude extract with highly significant differences at p<0.001between the group that were treated with crude extract only, the group treated with crude extract and exposed to H2O2, and the group exposed to H2O2 only as well as the group that were maintained in complete media. Bioactive compounds show the presence of vitexin and isovitexin following the HPLC method. Conclusion. High antioxidant activities and low toxicity effect of this crude revealed its high benefit to be used as natural medicine/supplements.